Avaliação de práticas de manejo nos atributos químicos e na perda de solo em região semiárida - Oliveira, André Luiz Torres de (2015)
Soil and climatic characteristics of the semi-arid region, associated with nonconservationist practices of use and management, make the environment susceptible to erosion. The conservation management practices represent alternatives to conventional systems in semi-arid regions, which may reduce losses by erosion and improve physical, chemical and biological aspects of the soil. It is assumed that the windrowing of twigs in level and agroforestry result in better soil chemical conditions and in lower production of sediments after rainfall events when compared with fallow areas. The downhill cultivation may result in worse soil chemical conditions and in higher production of sediments after rainfall events when compared with fallow areas. Therefore, the objective of this work was to evaluate the effects of management practices on soil chemical properties, as well as on surface runoff and on the production of sediments in the semi-arid region. The study was performed in a traditional Quilombola community (Brazilian hinterland settlement founded by people of African origin) in the city of Tamboril (CE). The management practices studied were MF1 – maize and beans cultivation with windrowing of twigs in level; PMB2 – downhill cultivation of cactus pear; PMF3 – cultivation of cactus pear intercropped with maize and beans with windrowing of twigs in level, and SAF4 – agroforestry system. Each management practice was compared to an adjacent area of natural regeneration (fallow area). Information on the production of sediments was obtained in portions of 1m² under regular rainfall conditions. Three portions were installed in each study area, in a total of 24 portions, in which collections were held from February to June 2015, which corresponds to the rainy season of the region. The collections needed to determine the surface runoff volume and the carried sediments were performed after each erosive rainy event, in the period of 24 hours. Soil samples were collected at random spots of each area in depths of 0-0.05 and 0.05-0.10 m with 5 repetitions each, in a total of 80 samples. Values of pH, macronutrients (Ca, Mg, P, K) levels, micronutrients (Fe, Zn, Cu e Mn) and sodium (Na) levels were determined, besides percent aluminum saturation (m%), sum of the bases, cation exchange capacity (CEC), percent base saturation (V%) and fractionation of organic matter (fulvic and humic acids and humin) with quantification of carbon (C) and nitrogen (N) of each fraction. Based on the results of this research, it was found that the management areas MF1 and PMB2 had higher soil loss (2,420.24 and 8,647.09 g, respectively) and water loss (203.14 and 224.33 L, respectively) than the areas PMF3 and SAF4 (832.56 and 355.17 g of soil loss; 153.33 e 199.40 L of water loss). Regarding the management areas and their respective fallow areas, it was observed that MF1 presented a soil loss of 63.27% higher than R1, and for the PMB2 area, this difference was of 73.01% compared to R2. The smallest variations were found in areas PMF3 and SAF4 with 9.54% and 8.73% more of soil loss when compared to their respective fallow areas, R3 and R4. The intercropped system PMF3 (cactus pear, maize and beans with windrowing of twigs in level) and SAF4 (agroforestry system) were as efficient as the fallow areas (R3 and R4) when it comes to controlling soil and water losses. There was no effect of the windrowing of twigs in level on the improvement of soil chemical properties in areas MF1 and PMF3; however, for the agroforestry system, improvements on soil in terms of organic carbon (OC) and phosphorus (P) levels were found.